An Analysis of Japanas Popular Cultural Tourism: Constructing Japanas Self-Image as a Provider of aoUniquea Culture (Global Journal of Human-Social Science, 2013)
Japan and its people are, and in some case, it suggests how they should behave accordingly. This paper analyzes the relations of identity, culture and tourism development in Japan. I argue that the promotion of Japan's tourism is closely linked to the establishment of particular images of itself or how the Japanese see themselves, i.e., self-image. The Japanese government has paid attention to tourism development for the last few years amidst its declining economy. Japanese tourist developers and entrepreneurs have collectively been interested in constructing a Japanese brand, namely "Cool Japan" with emphasis on popular culture. I will examine Japan's soft power through its growing interest in the development of pop cultural tourism. To build tourism all over Japan without delay, the popularity of modern Japanese culture becomes an effective marketing tool for local events, festivals, restaurants and other types of businesses. However, this is also to suggest that Japan's overemphasis on popular culture could lead to the devaluation of the country's tradition and history instead of economic prosperity.